Konsep Dasar Perilaku Organisasi: Definisi, Sejarah, dan Kontribusinya Pada Pengembangan Sumber Daya Manusia dalam Dunia Pendidikan - Saidah, Nyai; Hadi, Rusydan Abdul; Suharyat, Yayat (LPPM Institut Pendidikan Nusantara Global, 2024)
This journal explores the fundamental concepts of organizational behavior, focusing on its definition, history, and contributions to human resource development in the field of education. Employing a qualitative method and a literature review approach, this research delves into various definitions of organizational behavior that have evolved over time and outlines its historical evolution. Moreover, the journal investigates the contributions of organizational behavior to human resource development, particularly within the educational context. By detailing relevant theories and expert perspectives, this study provides in-depth insights into how the concept of organizational behavior can be applied to enhance the quality of teaching and learning. The implications of these findings can aid in designing more effective and sustainable educational strategies. In general, this research shows that basic concepts of organizational behavior have a significant impact in shaping inclusive and empowering educational environments. The implications of these findings can provide guidance for policy makers, education managers, and practitioners to better understand and apply the concept of organizational behavior effectively in the educational context.